2020
DOI: 10.46903/gjms/18.03.875
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and in Vivo Evaluation of Ph Sensitive Hydroxypropyl Methyl Cellulose-Graft-Acrylic Acid Hydrogels for Sustained Drug Release of Model Drug Nicorandil

Abstract: Background: Anti hypertensive drugs like “Nicorandil” require frequent dosing due to their shorter half-life. Such drugs are also pH sensitive, due to which greater portions of these drugs are degraded in acidic pH of stomach resulting in lesser bioavailability. The objective of this study was to formulate graft polymeric carrier system for sustained delivery of nicorandil to minimize dosing frequency and enhance patient compliance. Materials Methods: This animal model study was conducted in Department of Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…By recording the FTIR, the spectra of the drug confirmed that the model drug was evenly distributed within hydrogels. The FTIR spectra of the crosslinker, the monomer, and the polymer were also recorded to determine the uniform distribution of all these ingredients in linseed-based hydrogel [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…By recording the FTIR, the spectra of the drug confirmed that the model drug was evenly distributed within hydrogels. The FTIR spectra of the crosslinker, the monomer, and the polymer were also recorded to determine the uniform distribution of all these ingredients in linseed-based hydrogel [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Formulation M1 showed 71.71 % drug release at pH 7.4 while M2 showed 82.99 % release within 24 hrs, so formulation M2 was considered to have best drug release profile. In these polymeric network formulations, drug release pattern was directly related to AA content (Rashid et al, 2020). It was observed that all formulations followed Korsmeyer-Peppas kinetic model.…”
Section: In Vitro Drug Releasementioning
confidence: 90%